2016
DOI: 10.6007/ijarafms/v6-i2/2075
|View full text |Cite
|
Sign up to set email alerts
|

The Causality between Healthcare Resources and Health Expenditures in Turkey. A Granger Causality Method

Abstract: The aim of this study was to evaluate the causality between healthcare resources and health expenditure in Turkey over the period from 1975 to 2013. The empirical modeling was based on how GDP per capita, the number of doctor and number of hospital beds had an impact on the growth of health spending per capita. Data were gathered from the statistical databases of Turkstat, World Bank Indicators and OECD Health Data. Granger Var method was used to investigate causality between variables. Eviews 9 software was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The same outcome was discovered between spending on health and number of doctors as causality ranges from spending on health to number of doctors. There was no causality in their research, however, between health expenditure and amount of hospital beds [28].…”
Section: Literature Reviewmentioning
confidence: 92%
“…The same outcome was discovered between spending on health and number of doctors as causality ranges from spending on health to number of doctors. There was no causality in their research, however, between health expenditure and amount of hospital beds [28].…”
Section: Literature Reviewmentioning
confidence: 92%
“…Nevertheless, from available literature, there is a limited number of studies [12][13][14][15], that analyzed the effect of macroeconomic factors on public health costs. Similarly, Taskaya, Demirkiran [16] examined the association between healthcare expenditure, inflation and gross domestic capita per (GDPPc) in Turkey using data from the World Bank and Organisation for Economic Co-operation and Development (OECD) Health Database between 1975 to 2013. The study found no relationship between health expenditure, inflation rate and GDP per capita utilizing the granger causality approach.…”
Section: Introductionmentioning
confidence: 99%